A qualitative thematic review: emotional labour in healthcare settings. (27th July 2015) - Riley, Ruth; Weiss, Marjorie C.
Abstract: Aims: To identify the range of emotional labour employed by healthcare professionals in a healthcare setting and implications of this for staff and organisations. Background: In a healthcare setting, emotional labour is the act or skill involved in the caring role, in recognizing the emotions of others and in managing our own. Design: A thematic synthesis of qualitative studies which included emotion work theory in their design, employed qualitative methods and were situated in a healthcare setting. The reporting of the review was informed by the ENTREQ framework. Data sources: 6 databases were searched between 1979–2014. Review methods: Studies were included if they were qualitative, employed emotion work theory and were written in English. Papers were appraised and themes identified. Thirteen papers were included. Results: The reviewed studies identified four key themes: (1) The professionalization of emotion and gendered aspects of emotional labour; (2) Intrapersonal aspects of emotional labour – how healthcare workers manage their own emotions in the workplace; (3) Collegial and organisational sources of emotional labour; (4) Support and training needs of professionals Conclusion: This review identified gendered, personal, organisational, collegial and socio‐cultural sources of and barriers to emotional labour in healthcare settings. The review highlights the importance of ensuring emotional labour is recognized and valued, ensuring support and supervision is in place to enable staff to cope with the varied emotional demands of their work.